Changes in sprint force-velocity profile in international para footballers - Peña-González, I.; Javaloyes, A.; Sarabia, J. M.; Moya-Ramón, M. (International Journal of Sports Physiology and Performance, 2023)
Cerebral palsy (CP) football is a worldwide practiced para sport, which is played by people with CP, acquired brain injury, or stroke (according to the International Federation of Cerebral Palsy Football Classification Rulebook).1 To be eligible to play CP football, players must have a minimum impairment of hypertonia, athetosis, or ataxia with an impact on their abilities related to game performance.1 CP football is a 7-a-side modality of football in which time (30-min halves) and field size (70 m × 50 m) are reduced compared with regular football. Nevertheless, the literature has shown that the main physical actions that determine a high performance (eg, accelerations, sprints, or changes of direction among others) are the same as in regular football.2,3 Both regular and CP football are intermittent sports in which the aforementioned short and high-intensity actions, which are responsible for players` high performance, are alternated with low-intensity recovery periods.2 Players` physical performance in these determinant actions is usually assessed by linear-sprint, jump, and/or change-of-direction tests,4-7 whereas the ability to resist the repetition of these high-intensity efforts is usually assessed with intermittent endurance tests (eg, the Yo-Yo Intermittent Recovery Test or the 30-15 Intermittent Fitness Test).8 An increase in the number of CP football practitioners5 together with the increasing interest in physical performance assessment in CP football has been reflected in a high number of scientific publications in CP football during the past years. Most of these publications regarding CP football players` physical performance evaluation have been made under the "evidence-based classification criterion/perspective," which has been the basis of the improvement of the players` classification process.4-6,9,10 However, parallel to this, new research studies regarding the assessment of CP football players` physical performance have tried to show players` conditioning profiles, their adaptations to the training, or even talent identification and selection processes.